Copyright Illustration Image by Artificial Intelligence - Marsya Respati, Avifah Annisa; Wardana Mamonto, Andry Wikra; Aswari, Aan (Intellectual Law Review (ILRE), 2025)
This research aims to find out and analyze the legal protection of creators whose data is used as a reference by Artificial Intelligence (AI) in making illustrative images and how copyright arrangements for illustrative images produced using AI. This research uses normative juridical research methods by conducting literature study research in the form of Law Number 28 of 2014 concerning Copyright and literature related to the issues raised in this study. The results of this study indicate that the legal protection of creations used as AI references is automatically protected, but it is better if the creator licenses his work that is published in general. Also, illustrative images produced using AI cannot be categorized as Creation protected by the Copyright Law because AI is a computer system/program that cannot be equated with the Creator. It is recommended that the government immediately make changes to the Copyright Law as a consideration of the current development of AI in Indonesia in order to anticipate the imbalance between the Creator / Copyright Holder and the development of AI that uses Creation as a reference in producing new works, the need for innovation or new rules that focus on legal views related to AI that are developing in Indonesia in order to minimize the occurrence of a legal vacuum that can cause chaos in Indonesia.